PENGARUH LATIHAN SEPEDA SANTAI TERHADAP TEKANAN DARAH: Latihan, sepeda santai, tekanan darah - Hakim, Luqmanul (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2011)
In a normal, healthy adult, the heart was working well and which are not diseased blood vessels, has a systolic pressure 120 and diastolic pressure 80. Blood pressure is usually written 120/80. If the blood pressure is above 140/90 mm Hg up then the person is a patient of hypertension. And vice versa if the blood pressure is below 120/80 mm Hg then the person is a blood pressure hypotension. Otherwise normal blood pressure is 120 / 80-140 / 90 mm Hg. With age will be more prone to the risk of various diseases in which the limitation of motion, the density of the activities may prevent us from doing exercise. Exercise bikes are relaxed is aerobic exercise, due to the relaxing bike to lose weight, maintain a healthy heart and lungs, improving overall endurance, improve blood circulation and keep the cells - muscle cells. Based on the definition above, in this study there was no effect centered leisurely bicycle exercise on blood pressure. This study aimed to find out is there any influence blood pressure before and after relaxing bike. The problem in this study can be formulated as follows: Are there influences blood pressure before and after relaxing bike. This research method uses the study population, with a leisurely bike exercise independent variables and the dependent variable blood pressure. The population in this study are members of the association resident ancient nobility village bicycle taken purposively Kloposepuluh aged 40-60 years with a sample of 20. Blood pressure data collected by using a blood pressure test spygnomanometer. By t-test analysis results obtained t-count systole -1.515 oft- Table 8.907 at significance level 0.975, dk 19, from these results it can be concluded that: There is no effect on systolic cycling exercise but no effect on diastolic blood pressure. So in other words there is no difference in systolic blood pressure but diastolic is no difference before and after cycling exercise.